Clinical Case Series on Madhumegam (Type 2 Diabetes Mellitus) Management Using the Siddha Herbal Medicine: Keezhanelli Chooranam (KNC) - Soruban, T.; Sathiyaseelan, V. (International Journal of Pharmacy Research & Technology, 2026)
According to the 2021 World Bank report, the prevalence of diabetes in Sri Lanka was 11.3% among adults aged 20 -79 years. In Siddha literature, Madhumegam is correlated with Diabetes Mellitus and is classified under Meganoi in Yugi Vaithiya Cinthamani 800, belonging to the Pitha type (Thithippu Neer). Keezhanelli Chooranam (Phyllanthus amarus) is a single-herb formulation documented in the Siddha Pharmacopoeia of India for managing Madhumegam (Type 2 Diabetes Mellitus). To scientifically validate its traditional claim, a clinical study was conducted at the Siddha Teaching Hospital, Kaithady, with ethical approval from the Bandaranaike Memorial Ayurveda Research Institute. Six patients diagnosed with Madhumegam were enrolled. Keezhanelli Chooranam (5 g twice daily before meals with warm water) was administered for 90 days, along with a prescribed dietary regimen. Fasting Blood Sugar (FBS) was measured every 14 days, while Postprandial Blood Sugar (PPBS) and HbA1c were assessed at baseline and on Day 90. Statistical analysis using the paired t-test revealed a highly significant reduction in PPBS (p = 0.008) and a significant decrease in VLDL (p = 0.015). Although reductions in FBS (↓32 mg/dL), HbA1c (↓0.94%), and Triglycerides (↓43 mg/dL) were not statistically significant (p = 0.065–0.068), they indicated meaningful clinical improvement. No adverse changes were observed in Total Cholesterol, HDL, LDL, or Hemoglobin levels. The findings suggest that Keezhanelli Chooranam possesses anti-hyperglycemic and hypolipidemic properties, providing preliminary scientific evidence supporting its Siddha claim in managing Madhumegam. Further validation through large-scale randomized controlled trials is recommended.
Keywords: Fasting blood glucose; Hba1c; Keezhanelli chooranam; Madhumegam; Postprandial blood glucose; Total cholesterol; Type 2 biabetes mellitus.